Informal vendors and food systems planning in an emerging African city. (August 2021) - Giroux, Stacey; Blekking, Jordan; Waldman, Kurt; Resnick, Danielle; Fobi, Daniel
Highlights: Informal food vendors expand the spatial footprint of the urban food system. Informal food vendors facilitate cross-scale food system linkages. Informal food vendors are integrated into urban food systems, but not policy-wise. Vendors should be viewed as assets for urban food systems planning in Africa. Abstract: Rapid urban growth is straining infrastructures, economies, and food security of cities in sub-Saharan Africa (SSA). Amid competing issues of sanitation, housing, and unemployment, planning for urban food security receives less attention. Despite the proliferation of supermarkets in SSA, informal food vendors remain crucial sources of food for the majority of households. However, as cities grow and planners try to adapt, these informal vendors are generally left out of planning considerations, marginalized by policies that do not support this business model, or subjected to political vicissitudes. This paper analyzes how vendors in emerging cities are economically, socially, and spatially integrated within the urban food system, highlighting the assets these vendors represent and the ways they might support growth in cities. We map vendors' networks of food suppliers, and describe sources of operating capital and labor assets to show the range of services vendors utilize and the types of institutions, businesses, and individuals that vendors use to support their work. We spatially analyze the relationship between vendors and suppliers, and between vendors and households, to demonstrate how enmeshed these vendors are in the broader food system and the links they create between consumers and suppliers. We demonstrate that due to spatial differences and vendors' and consumers' needs in emerging cities, a one-size-fits-all approach for integration of informal vendors in the food system is less likely to be successful in terms of either economic development or household food security.